Effect of additive volume fraction on a fluid film pressure and load of hydrodynamic journal bearing using ferromagnetic fluid - Omer, M.A. (Asian Research Publishing Network, 2016)
The fundamental objective of this work is to investigate the performance of Ferrolubricants under a combined effect of magnetization and fluid behaviors. Two types of fluid models were investigated for further improvement of hydrodynamic journal bearing performance. Lubrication of finite hydrodynamic journal bearing lubricated by ferromagnetic fluids under the influence of Power-law and Couple-stress fluid models. By taking into account additives volume fraction, magnetization effect by the magnetic coefficient and fluid models (Power-law and Couple-stress) due to the microstructure additives. The fundamental approach involves a general modified form of Reynolds equation. The results showed an increase of pressure distribution within the fluid film whereby load carrying capacity of the hydrodynamic journal bearing improved. Â© 2006-2016 Asian Research Publishing Network (ARPN).